Faradaic Fenton Pixel: Reactive Oxygen Species Delivery Using Au/Cr Electrochemistry - Miglbauer, Eva; Abdullaeva, Oliya S; Gryszel, Maciej; Głowacki, Eric Daniel (Chembiochem, 2023)
Reactive oxygen species (ROS) are an integral part of many anticancer therapies. Fenton-like processes involving reactions of peroxides with transition metal ions are a particularly potent and tunable subset of ROS approaches. Precise on-demand dosing of the Fenton reaction is an area of great interest. Herein, we present a concept of an electrochemical faradaic pixel that produces controlled amounts of ROS via a Fenton-like process. The pixel comprises a cathode and anode, where the cathode reduces dissolved oxygen to hydrogen peroxide. The anode is made of chromium, which is electrochemically corroded to yield chromium ions. Peroxide and chromium interact to form a highly oxidizing mixture of hydroxyl radicals and hexavalent Cr ions. After benchmarking the electrochemical properties of this type of device, we demonstrate how it can be used under in vitro conditions with a cancer cell line. The faradaic Fenton pixel is a general and scalable concept that can be used for on-demand delivery of redox-active products for controlling a physiological outcome.
Keywords: oxygen reduction reaction; reactive oxygen species; bioelectronics; Fenton reaction